Challenges faced by mothers of children with cerebral palsy (cp) attending the Jairos Jiri Association (JJA) first-step inclusive pre-school, in Bulawayo - Chibvongodze, Talent (Midlands State University, 2018)
This study aimed to explore challenges faced by mothers of children with cerebral palsy (CP) attending the Jairos Jiri Association (JJA) First-Step Inclusive Pre-school, in Bulawayo. Relevant literature was reviewed, inclusive of Bourdieu’s theory of practice which formed the theoretical framework of the study. Previous studies were discussed from which a knowledge gap was identified. The researcher used a qualitative research paradigm and an exploratory design. Targeted were mothers of children with CP attending JJA First-Step Inclusive Preschool, in Bulawayo. Stratified sampling was used with a population sample of 12 mothers. Data was collected using semi structured in-depth interviews which were presented using descriptive analysis and analysed using thematic analysis. The researcher observed ethics which included informed consent, anonymity, confidentiality and privacy. Major findings were that mothers of children with CP faced psychological, social and financial challenges. Recommendations made included that there was need for the government, non-governmental organisations, relatives and the community to offer mothers social, emotional, and financial support and to raise disability awareness so as to reduce stigma and discrimination.